PENGEMBANGAN MODEL ON THE JOB TRAINING BERBASIS ANDRAGOGI UNTUK PENINGKATKAN KOMPETENSI PENDIDIK ANAK USIA DINI NONFORMAL - Misran Rahman (Jurnal Ilmiah Visi, 2011)
This research on the development of on the job training model based on andragogy is related to the efforts to improve the competence of early childhood education. The research, related to the effort to enhance the competences of early childhood education tutors, aimed at developing the model and its effects on the early childhood education tutors’ competences. In developing the model, the research included quantitative and qualitative methods. After testing the model, the research concluded that it is effective in fostering the competences of early childhood education tutors. Based on the research findings, this model is recommended to disseminated to develop the competences of early childhood education tutors. The development of this model has an implication for the fulfillment of competence standards of early childhood education tutors.